2016
DOI: 10.18844/cjes.v11i1.266
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of computers on vocabulary learning among preschool children: a semiotic approach

Abstract: Semiotics in foreign language learning has recently achieved some prominence as a theoretical foundation for language teaching and learning. Although there have been a number of research on the semiotics in foreign language learning, the practical use of semiotics in preschool classroom environment still remains unanswered. What is more, the effectiveness of computers on vocabulary learning among preschool children is still an obscure area, which attracts the attentions of researchers, scholars and practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
2
6
0
1
Order By: Relevance
“…They also in line with the findings of Gonzalet et al, (2011) who found that students in the experimental group scored higher than the students in the control group in the standardized measure of receptive vocabulary. In addition, the study supports the findings of Basoz and Can (2016) who stated that the use of this technique in vocabulary teaching makes the learning environment more motivating and interesting.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…They also in line with the findings of Gonzalet et al, (2011) who found that students in the experimental group scored higher than the students in the control group in the standardized measure of receptive vocabulary. In addition, the study supports the findings of Basoz and Can (2016) who stated that the use of this technique in vocabulary teaching makes the learning environment more motivating and interesting.…”
Section: Resultssupporting
confidence: 86%
“…Not only vocabulary that can be taught through the semiotic approach, but all the four skills, listening, speaking, reading, and writing in Arab World English Journal www.awej.org ISSN: 2229-9327 292 ELT. In fact, semiotics is no longer counted as an unfamiliarized approach in the field of education; instead, it has recently achieved some significance as a theoretical foundation for foreign language learning/ teaching (Basoz & Can, 2016). There are a few studies done on the effect of semiotics on vocabulary learning and teaching.…”
Section: Semiotics and Vocabulary Learning/teachingmentioning
confidence: 99%
“…Fidan, 2003;Eren, 2015;Güvendir & Gezgin, 2015;Kurt & Bensen, 2017;Özer & Koçoğlu, 2017). In contrast, there exist some contradictory findings, too, reporting that no significant difference exists between the instruction with or without technology in foreign language vocabulary learning (Tokaç, 2005;Erkuş, 2008;Basoz & Can, 2016). In order to deal with such contradictions in the existing research, a synthetic analysis is required to get a fuller picture of how effective digital technologies are in foreign language learning in this country.…”
Section: Technology-mediated Vocabulary Learningmentioning
confidence: 99%
“…Extensive theoretical and conceptual frameworks have yet to be found that explain the relationships between the characteristics of rapid and, at times, groundbreaking technological developments and their role in the users' daily lives and educational potentials (Basöz & Can, 2016;Ozcan & Bicen, 2016;Pachler, Bachmair, & Cook, 2010;Saran & Seferoğlu, 2010). However, mobile learning is becoming increasingly widespread both in the scope of "formal" and "non-formal" education and has gained significance by attracting the interest and attention of practitioners and researchers in all areas of education.…”
Section: Introductionmentioning
confidence: 99%